Portugal’s Integration in World Trade: A Gravity Model - Camacho, P. (2013)
The aim of this study is to evaluate the integration of Portugal in terms of international trade in a world where trade barriers have been blurred. More specifically, the aim is to identify and quantify the factors that benefit or harm the Portuguese international trade. For this purpose it was used the standard gravity model methodology. This paper presents a summary of the literature on international trade theory, stylized facts of Portuguese international trade and literature regarding the gravity model of international trade. The Portuguese exports and imports were analyzed by using the standard gravity model methodology. In order to do so, two different standard gravity models were employed: one applied to exports and another to imports. Both models consider the following variables: GDP, GDP per capita, Distance, Common Border, Common Language, Landlocked, European Union (EU) and Eurozone (EZ). The results suggest that the participation of Portugal in the EU and in the Community of Portuguese Language Countries (CPLP) are important for both exports and imports. However, the results do not allow us to say that the participation of Portugal in the EZ has resulted in advantages for Portuguese exports destined for the EZ countries.